Effect of stem cell therapies on tendon-bone healing after anterior cruciate ligament reconstruction in animal models: Protocol for a systematic review and meta-analysis - Shibo Zhao; Congcong Wang (PLoS ONE, 2026)
Introduction Anterior cruciate ligament (ACL) reconstruction is widely performed, yet insufficient tendon-bone healing remains a key contributor to graft failure. Stem cell-based interventions, including mesenchymal stem cells (MSCs) and stem cell-derived products (e.g., exosomes/extracellular vesicles), have shown potential to enhance tendon-bone integration in preclinical models. However, findings across animal studies are heterogeneous and have not been comprehensively synthesized. This review aims to evaluate the effects of stem cell-based therapies on tendon-bone healing after ACL reconstruction in animal models. Methods and analysis This protocol follows PRISMA-P. We will search PubMed, Embase, Scopus, SPORTDiscus, Web of Science, and the Cochrane Library from inception to the final search date. Controlled animal studies comparing ACL reconstruction with stem cell-based interventions versus controls will be included. Primary outcomes are biomechanical properties (ultimate failure load and stiffness). Secondary outcomes include micro-CT measures of bone integration (e.g., bone volume fraction, bone mineral density) and histological outcomes (e.g., interface maturation or validated scoring systems). Risk of bias will be assessed using SYRCLE’s tool. Random-effects meta-analyses will be performed, with prespecified subgroup analyses by stem cell type, delivery method, animal species, and follow-up time. Sensitivity analyses and publication-bias assessments will be conducted where appropriate. PROSPERO registration CRD420251137985.